DIAGNOSTIC AND THERAPEUTIC MODALITIES IN THE MANAGEMENT OF A PATIENT WITH OCULAR SURFACE SQUAMOUS NEOPLASIA (OSSN)-CASE REPORT AND REVIEW - Nikolovska, Biljana; Duma, Christijan; Pandilov, Stefan; Risteski, Vladimir; Todorovska, Magdalena Bogdanovska; Petrusevska, Gordana (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Ocular surface squamous neoplasia (OSSN) is a clinical term that includes epithelial dysplasia of various degrees, carcinoma in situ to invasive squamous cell carcinoma of the conjunctiva. Several procedures are used today to diagnose these lesions: biopsy with pathohistological analysis, cytology, in vivo confocal microscopy, ultrasound biomicroscopy, AS-OCT (Optical Coherence Tomography of the Anterior Segment) and OCT-A (Optical Coherence Tomography-Angiography). Aim: To present the possible diagnostic and therapeutic modalities that are used today in dealing with OSSN, as well as to optimize the management of these lesions in everyday clinical practice, in order for the patient to receive appropriate treatment. Case report, methods and results: In this paper we present the case of a 71-year-old patient, presented for an ophthalmological examination last year at the Clinic for Eye Diseases in Skopje. The patient reported a foreign body sensation and irritation of the right eye due to a tumor formation in the temporal limb that was gradually increasing over the past two years. Biomicroscopic examination and AS-OCT established a clinical diagnosis of OSSN. The lesion was excised and sent to the Institute of Pathology in Skopje, pathohistologically confirmed for in situ carcinoma of the conjunctiva. Conclusion: AS-OCT, surgical excision, and pathohistological examination are the "optimal triad" in the management of these lesions. Keywords: ocular surface squamous neoplasia, OSSN, carcinoma in situ , pathohistology, Optical Coherence Tomography of the Anterior Segment.